Stress Analysis of the Interface Reaction Layer Between Ni–P Films and GaAs Substrate After Annealing - Koichiro NISHIZAWA; Ayumu MATSUMOTO; Yasuyuki NAKAGAWA; Hitoshi SAKUMA; Yoshiki KOJIMA; Naoki FUKUMURO; Shinji YAE (Electrochemistry)
Electroless Ni–P plating films, used as the seed layers for the backside electrodes of gallium arsenide (GaAs) semiconductor devices, cause substrate warping (wafer warpage) during annealing, leading to substrate cracking and chipping. In this study, Ni–P films with different P concentrations (6, 17, and 20 at%) were deposited on a GaAs substrate, and the wafer warpage was analyzed after annealing at 240 °C for 1 h. The wafer warpage showed a reduction in size with an increase in P concentration in the as-deposited Ni–P film. Cross-sectional observations revealed the formation of a reaction layer at the interface between Ni–P and GaAs after annealing, and its thickness decreased with increasing P concentration. X-ray photoelectron spectroscopy revealed that the reaction layer was a Ni3GaAs alloy. The Ni atoms in the Ni–P films diffused to the GaAs substrate, and the P concentration in the Ni–P layers increased to a constant value (31–33 at%). X-ray diffraction measurements indicated that the Ni–P layers crystallized to Ni12P5 upon annealing because of the increase in P concentration owing to Ni diffusion. To evaluate the contribution of the reaction layer to the wafer warpage, the Ni–P layer was removed by ion milling, and the wafer warpage was measured. The estimated stress of the reaction layer was 580 MPa. From the calculation of the contribution of each layer to the wafer warpage, it was found that the Ni3GaAs layer largely contributed to the wafer warpage.